The joy of annual reviews - SHERYL BARRINGER (Academic Chairpersons Conference Proceedings, 2020)
Annual reviews of faculty and staff are a valuable tool to inspire and learn more about the amazing people you supervise. They are also a critical time to enforce expectations and consequences. We will discuss subtle ways to increase productivity as well as the steps when termination is warranted.
Keywords: Faculty performance; productivity; termination; staff; expectations; reviews